Review on Frankincense Essential Oils: Chemical Composition and Biological activities - Sura M. Abbood1*,Sura Mohammed Kadhim2, Aziz Yasir Hasan Al-Ethari3, Zyad H AL-Qaisia1, Mustafa Taha Mohammed1 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
Frankincense plant is one of the most widely used groups of medicinal herbs and has been extensively used due to the biological activities it possesses. Recently, a considerable literature has developed around the theme of frankincense and its different components, alongside with numerous researches published on its historical role in curing various chronic diseases. The present review has focused on the chemical ingredients of frankincense essential oil and pharmacological activities of these components. Essential oils (EOs) are known to have anti-inflammatory and antiviral effects in addition to what being suggested about having activity against virus of SARC-CoV-2. These activities, which attributed to different chemical ingredients such as phenolic monoterpenes could have a protection and/or relief of some illnesses. The current study provides reference for further research in attempt to become a relevant basis of development for new remedies to combat chronic disease and viral infection such as Coronavirus.